2013
DOI: 10.1186/1756-0500-6-480
|View full text |Cite
|
Sign up to set email alerts
|

Gout with auricular tophi following anti-tuberculosis treatment: a case report

Abstract: BackgroundAuricular tophi are firm deposits of monosodium urate in crystal form, which may slowly develop in subcutaneous tissue of the ear. Ear is not usual locations for gout tophi, but when this growth does occur, helix and the antihelix are common sites.Case presentationWe present a 64-year-old man who had multiple painless nodules over bilateral helix. An excisional biopsy was performed. Hematoxylin-eosin staining of biopsy specimens revealed a proteinaceous matrix that surrounded dissolved crystals, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Clinically, the differential diagnosis included sebaceous cyst, epidermal and dermoid cyst, chondrodermatitis nodularis helicis, actinic keratosis, keloid, verruca vulgaris, amyloids, elastotic nodules, weathering nodules, rheumatoid nodules, sarcoid nodules, tophaceous gout, sarcoidosis, leishmaniasis, leprosy, skin neoplasia including hemangioma, keratoacanthoma, chondroma, lipoma, schwannoma, neurolimemmoma, or even malignancies such as basal cell caricinoma or squamous cell caricinoma. 7) A pathological examination is important to rule out the possibility of malignancy. In this case, we were able to suspect AT from the beginning, because a thorough questioning of medical history revealed that the patient had a long standing history of uncontrolled gout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, the differential diagnosis included sebaceous cyst, epidermal and dermoid cyst, chondrodermatitis nodularis helicis, actinic keratosis, keloid, verruca vulgaris, amyloids, elastotic nodules, weathering nodules, rheumatoid nodules, sarcoid nodules, tophaceous gout, sarcoidosis, leishmaniasis, leprosy, skin neoplasia including hemangioma, keratoacanthoma, chondroma, lipoma, schwannoma, neurolimemmoma, or even malignancies such as basal cell caricinoma or squamous cell caricinoma. 7) A pathological examination is important to rule out the possibility of malignancy. In this case, we were able to suspect AT from the beginning, because a thorough questioning of medical history revealed that the patient had a long standing history of uncontrolled gout.…”
Section: Discussionmentioning
confidence: 99%
“…6) However, a PubMed search yielded just a few articles specifically addressing ATs (Table 1). [1][2][3]5,[7][8][9][10][11][12][13][14] Interestingly, all of the patients were male. Gout itself, is more common in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with gout may also present a cutaneous involvement, characterised by the development of intradermal or subcutaneous nodules as a sign of the tophi deposition. They are typically described in avascular tissues, such as in the ears (helix and antihelix areas) or in the periarticular acral areas, where they are often associated with an involvement of bursae or tendons [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the dose of febuxostat ameliorated the nodule by reducing the serum UA for five months. Since auricular nodules are involved in various disorders, including skin neoplasms, rheumatoid arthritis and sarcoidosis, a biopsy should be performed (1). Despite his refusing a biopsy, pinna tophus was diagnosed given that the nodule had developed on the antihelix and disappeared with urate reduction.…”
mentioning
confidence: 99%